The influence of kinesiology tape colour on performance and corticomotor activity in healthy adults: a randomised crossover controlled trial - Rocco Cavaleri; Tribikram Thapa; Paula R. Beckenkamp; Lucy S. Chipchase (BMC Sports Science, Medicine and Rehabilitation, 2018)
Abstract Background There exists conflicting evidence regarding the impact of kinesiology tape on performance and muscle function. One variable that may account for disparities in the findings of previous studies is the colour of the tape applied. Colour is hypothesised to influence sporting performance through modulation of arousal and aggression. However, few studies have investigated the influence of colour on products designed specifically to enhance athletic performance. Further, no studies have investigated the potential influence of colour on other drivers of performance, such as corticomotor activity and neuromuscular function. Thus, the aim of this study was to investigate the influence of kinesiology tape colour on athletic performance, knee extensor torque, and quadriceps neuromuscular function. Methods Thirty two healthy participants were assessed under five conditions, applied in random order: (1) no kinesiology tape (control), (2) beige-coloured kinesiology tape applied with tension (sham A), (3) beige-coloured kinesiology tape applied with no tension (sham B), (4) red-coloured kinesiology tape applied with tension, and (5) blue-coloured kinesiology tape applied with tension. Athletic performance was assessed using a previously validated hop test, knee extensor torque was measured using an isokinetic dynamometer, and transcranial magnetic stimulation was utilised to provide insight into the neuromuscular functioning of the quadriceps musculature. Results Kinesiology tape had no beneficial impact on lower limb performance or muscle strength in healthy adults. The colour of the tape did not influence athletic performance (F (4, 120) = 0.593, p = 0.669), quadriceps strength (F (4, 120) = 0.787, p = 0.536), or neuromuscular function (rectus femoris: F (2.661, 79.827) = 1.237, p = 0.301). Conclusion This study found that kinesiology tape does not alter lower limb performance or muscle function in healthy adults, irrespective of the colour of the tape applied. Future research should seek to confirm these findings beyond the research setting, across a range of sports, and at a range of skill levels. Trial registration Australian New Zealand Clinical Trials Registry. ACTRN12616001506482. Prospectively registered on 01/11/2016.